Finite element modelling of blunt or non-contact head injuries - Lawson, A. R. (Cranfield University, 1997)
Safety is an increasingly important aspect of vehicle design. Legislation requires minimum levels of safety through full scale tests. Customers are provided with information regarding the safety performance of vehicles so that they can make an informed buying decision. Vehicle crashes were responsible for 40000 fatalities and 5.2 million non fatally injured patients in the US during 1994. The direct and direct cost of head injuries in the US is estimated at $25 billion per year. Injury criteria that can predict the severity of head injuries are important engineering tools for improving vehicle safety. At present the injury that the human head is subjected to is predicted by the Head Injury Criterion (HIC). This criterion is inadequate as it is not based upon a thorough understanding of the underlying head injury mechanisms. The important blunt or non-contact head injury mechanisms are diffuse axonal injury, bridging vein disruption and surface contact contusions. The severity of these injury mechanisms is hypothesised to be related to the level of motion of the brain with respect to the skull. Finite element modelling is used to analyse these head injury mechanisms. Models are developed which include all the relevant anatomical entities and detail. Accurate material property information and boundary conditions are used in the modelling to ensure that the head injury mechanisms can be accurately simulated. Tissue failure criteria are developed to link the various field parameters monitored during the simulations with injury severity. The models are then comprehensively validated with information obtained from pathological observations, cadaver experiments, accident reconstructions and volunteer data. These models are then used to determine the biomechanics of head injury and to develop improved head injury tolerance curves. The simulations demonstrate that head injury severity is dependent upon the magnitude, pulse duration and direction of the applied translational and rotational acceleration pulses.